2018
DOI: 10.1016/j.rmed.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Several high-resolution computed tomography findings associate with survival and clinical features in rheumatoid arthritis-associated interstitial lung disease

Abstract: Many radiological findings associate with the course of the disease of RA-ILD and could potentially be useful when planning the RA treatment or evaluating the risk of death in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…Radiological findings in RA-ILD include ground glass-opacities, reticulation, consolidation, honeycombing, and nodules similar to other ILD subtypes [30,33,38,39]. The most common HRCT patterns in RA-ILD are UIP and NSIP, while organizing pneumonia (OP) and bronchiolitis are less common ( Figure 1) (Table 1) [8,14,[38][39][40][41][42][43][44][45][46][47]. Studies show a fairly good correlation between HRCT and histopathological findings with the least concordance in the diagnosis of UIP and NSIP [39,42,46].…”
Section: Imagingmentioning
confidence: 99%
“…Radiological findings in RA-ILD include ground glass-opacities, reticulation, consolidation, honeycombing, and nodules similar to other ILD subtypes [30,33,38,39]. The most common HRCT patterns in RA-ILD are UIP and NSIP, while organizing pneumonia (OP) and bronchiolitis are less common ( Figure 1) (Table 1) [8,14,[38][39][40][41][42][43][44][45][46][47]. Studies show a fairly good correlation between HRCT and histopathological findings with the least concordance in the diagnosis of UIP and NSIP [39,42,46].…”
Section: Imagingmentioning
confidence: 99%
“…113 When compared with the other CTD, rheumatoid arthritis-associated ILD (RA-ILD) is more commonly associated with a UIP pattern, but NSIP can also be seen. [114][115][116] Irrespective of which CTD is involved, clinicians should note that an ILD can present as the first clinical feature of an underlying CTD. A previous retrospective study has reported almost one-third of consecutive ILD patient satisfied published criteria for an underlying CTD that was unrecognized during the initial assessment.…”
Section: Ctd-ildmentioning
confidence: 99%
“…19 Risk factors for ILD in RA include male sex, older age, smoking history, presence of rheumatoid factor, 19 and ACCPA. 20 The majority of patients with RA-ILD exhibit a usual interstitial pneumonia (UIP) morphology, 21 characterized on HRCT by basal predominant subpleural reticulation, with or without honeycombing (►Fig. 1).…”
Section: Parenchymal Diseasementioning
confidence: 99%
“…16 Of patients with RA and non-UIP ILD, a nonspecific interstitial pneumonia (NSIP) or unclassifiable HRCT morphologies are the next most common phenotypes, being present in around 10 to 15% of patients. 21,25,26 Fibrotic organizing pneumonias (OPs), lymphocytic interstitial pneumonias, and desquamative interstitial pneumonias (DIPs) are rare. 25 Rheumatoid pneumoconiosis (Caplan's syndrome) represents a characteristic HRCT morphology of fibrosis which occurs in the context of RA and occupational dust-related pneumoconiosis.…”
Section: Parenchymal Diseasementioning
confidence: 99%